(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The purpose of this study was to evaluate the “effectiveness of isometric exercises as compared to general exercises along with cervical spinal mobilization to reduce pain, disability and to increase range of motion in chronic non-specific neck pain”For this randomized controlled experiment total 32 patients (16 in each group) with chronic non-specific neck pain were recruited from physiotherapy Ward Mayo Hospital Lahore, Department of Physiotherapy King Edward Medical University Lahore between October, 2019 and March, 2020. Simple randomization method was used to assign participants into isometric exercise group and general exercise with cervical spine mobilization group. The isometric exercise group performed exercises for neck muscle groups with a rubber band and general exercises with cervical mobilization group performed active range of movement exercises for all neck movements. Patients in both groups received 4 supervised treatment sessions per week for 6 weeks. Visual Analogue Scale (VAS), Neck disability index Questionnaire and goniometer were used to assess pain, disability and neck range of movements at baseline and after 6 weeks.Both interventions showed statistically significant improvements in pain, function and range of movement p = 0.001for isometric exercise group, p = 0.05 for general exercises group and p= <0.001 for range of movement. However, mean improvements in post intervention VAS score and Neck disability index Questionnaire score was better in isometric exercises group as compared to general exercise group. In conclusion, both interventions are effective in the treatment of chronic non- specific neck pain however; isometric exercises are clinically more effective than general exercises with cervical spine mobilization.